Knowledge level of high risk of pregnancy with antenatal care visit compliance during pandemic - Catur Wulandari; Suherni Suherni; Nur Djanah (Jurnal Kesehatan Ibu dan Anak, 2022)
Non-compliance in the antenatal care can cause various types of high-risk pregnancies to be unknown which can affect the continuity of pregnancy or pregnancy complications so that they cannot be addressed immediately which will result in an increase in the Maternal Mortality Rate (MMR). This study was conducted to determine the relationship between the level of knowledge about the high risk of pregnancy in pregnant women and to compliance antenatal care visits during the pandemic. This research is an analytic observational research, using a cross sectional research design. The research subjects were 55 respondents at the Galur II Public Health Center, Kulon Progo in January 2022 using purposive sampling technique. The data that has been collected is then coded, then the data is processed using the SPSS application, using the chi-square statistical test with a 90% confidence degree (?=0.1). The results showed that 54.5% of respondents were high school/vocational high school graduates, 83.6% of respondents were between the ages of 20-35 years, 54.5% of respondents were pregnant with multiparas, and 74.5% of respondents had jobs as housewives. The results of statistical tests showed that as many as 30 respondents (93.8%) had good knowledge and were obedient in conducting antenatal care visits. Hypothesis testing with chi-square statistical test and obtained p value = 0.001 (<0.05). There is a relationship between the level of knowledge about the high risk of pregnancy in pregnant women and compliance with antenatal care visits during the pandemic.